A new global division of labour in venture capital flows: Coupang's IPO success at the New York Stock Exchange. Issue 2 (15th March 2023) - Oh, Ingyu; Koh, Yunsung; Kim, Yun Kyung
ABSTRACT: Coupang, which is an international spinoff of Softbank Vision Fund, chronicled a gargantuan IPO success at the New York Stock Exchange (NYSE) in 2021. Coupang is similar in many respects to Softbank's earlier accomplishment with Alibaba's IPO at the NYSE. By focusing on the success factors of the IPO at the NYSE and Coupang's domestic business in South Korea, we advocate four propositions on the nature of global venture capital firms that try to link actual e-commerce markets in East Asia with the global centers of IPOs in the US. This study also deals with corporate governance in the new e-commerce sector, political risks and labor union militancy in a host country, predictors and contextual conditions of IPOs at the NYSE and the dual class system of shares and financial structures in a host country.